Laboratory control values for CD4 and CD8 T lymphocytes. Implications for HIV-1 diagnosis. - Bofill, M (1992)
With the advent of standard flow cytometric methods using two-colour fluorescence on samples of whole blood, it is possible to establish the ranges of CD3, CD4 and CD8 T lymphocyte subsets in the routine laboratory, and also to assist the definition of HIV-1-related deviations from these normal values. In 676 HIV-1-seronegative individuals the lymphocyte subset percentages and absolute counts were determined. The samples taken mostly in the morning. The groups included heterosexual controls, people with various clotting disorders but without lymphocyte abnormalities as well as seronegative homosexual men as the appropriate controls for the HIV-1-infected groups. The stability of CD4% and CD8% values was demonstrated throughout life, and in children CD4 values less than 25% could be regarded as abnormal. The absolute counts of all T cell subsets decreased from birth until the age of 10 years. In adolescents and adults the absolute numbers (mean +/- s.d.) of lymphocytes, CD3, CD4 and CD8 cells were 1.90 +/- 0.55, 1.45 +/- 0.46, 0.83 +/- 0.29 and 0.56 +/- 0.23 x 10(9)/l, respectively. In patients with haemophilia A and B the mean values did not differ significantly. In homosexual men higher CD8 levels were seen compared with heterosexual men and 27% had an inverted CD4/CD8 ratio but mostly without CD4 lymphopenia (CD4 less than 0.4 x 10(9)/l). However, some healthy uninfected people were 'physiologically' lymphopenic without having inverted CD4/CD8 ratios. When the variations 'within persons' were studied longitudinally over a 5-year period, the absolute CD4 counts tended to be fixed at different levels. As a marked contrast, over 60% of asymptomatic HIV-1+ patients exhibited low CD4 counts less than 0.4 x 10(9)/l together with inverted CD4/CD8 ratios. Such combined changes among the heterosexual and HIV-1-seronegative homosexual groups were as rare as 1.4% and 3%, respectively. For this reason, when the lymphocyte tests show less than 0.4 x 10(9)/l CD4 count and a CD4/CD8 ratio of less than unity, the individuals need to be investigated further for chronicity of this disorder, the signs of viral infections such as HIV-1 and other causes of immunodeficiency.